The structure of perceptual experience - Stazicker, James; Ohio Library and Information Network (Chichester, West Sussex ; Malden, MA : John Wiley & Sons Inc., 2015)
"The Structure of Perceptual Experience articulate these various structural features, exploring their consequences for the nature of perceptual experience and the form of cognitive contact with the world it provides"--
Includes bibliographical references and index
Keywords: Perception (Philosophy); Representation (Philosophy); Electronic books